Difficulties in emotional regulation mediates the impact of burden on quality of life and mental health in a sample of family members of people diagnosed with Borderline Personality Disorder - Fonseca-Baeza, Sara; García-Alandete, Joaquín; Marco, José Heliodoro; Pérez Rodríguez, Sandra; Baños, Rosa M.; Guillén, Verónica (Frontiers in Psychology, 2023)
Although it has been suggested that family members of persons suffering from Borderline Personality Disorder (BPD) endure high levels of burden, however, the process and the impact of this burden in their lives, and specifically the relation between the burden and emotional regulation has not been broadly investigated among this population. The main objective of this study is to examine the impact of burden on quality of life and depression, anxiety and stress, as mediated by difficulties in emotional regulation in family members of persons diagnosed with BPD.Method. Participants were 167 family members of persons diagnosed with BPD. The Burden Assessment Scale, Difficulties in Emotion Regulation Scale, Multicultural Quality of Life Index, and Depression Anxiety Stress Scale-21 were filled out. Mediation analysis was conducted using the Maximum Likelihood estimator, bootstrap method and listwise deletion for missing data.Results. Burden showed a significant, negative effect on quality of life and positive on depression, anxiety and stress. Difficulties in emotion regulation significantly mediated these relations. After accounting for the mediating role of difficulties in emotion regulation, burden still had an impact on quality of life, depression, anxiety and stress. Women showed a higher level in both burden and stress than men. The caregivers with secondary and higher studies showed higher levels in burden than those with no studies. not signficant differences in burden, emotion regulation, depression, anxiety and stress were found related to marital status.2 Conclusion. Difficulties in emotion regulation mediate the relations between burden and quality of life, depression, anxiety, and stress. Family members could engage in group interventions designed specifically for family members of people with BPD, oriented toward understanding the disorder or learning skills.